"We have to take care of them": front office workers and the secret sexual encounters of guests in high-end hotels. Issue 4 (20th January 2022) - Gaspani, Fabio
Abstract : Purpose: In line with the escapist dimension of hospitality settings, the article investigates how the front office staff of high-end hotels deal with clients' secret sexual encounters. Design/methodology/approach: The article draws on data collected through a participant observation study conducted in two high-end hotels in Milan (Italy), during which the author held the role of front-line receptionist. Findings: The research illustrates the ways in which workers frame events and conduct operations to guarantee the appropriate conditions for guests' extra-marital adventures and paid sexual encounters. In revealing the role of shared knowledge as well as non-formalised procedures in meeting guests' needs, the article shows how employees seek to protect their own work and the hotel's image. Originality/value: The article sheds light on the very features of high-end service work by illustrating how workers satisfy clients' secret needs and unexpressed demands.